Plasma level and expression of visfatin in the porcine hypothalamus during the estrous cycle and early pregnancy - Tadeusz Kaminski (Nature Portfolio, 2021)
Abstract Visfatin appears to be an energy sensor involved in the regulation of female fertility, which creates a hormonal link integrating the control of energy homeostasis and reproduction. This study evaluates the expression levels of visfatin gene and protein in selected areas of the porcine hypothalamus responsible for gonadotropin-releasing hormone synthesis: the mediobasal hypothalamus (MBH) and preoptic area (POA), and visfatin concentrations in the blood plasma. The tissue samples were harvested from gilts on days 2–3, 10–12, 14–16, and 17–19 of the estrous cycle, and on days 10–11, 12–13, 15–16, 27–28 of pregnancy. Visfatin was localized in the cytoplasm and nucleus of cells creating both studied hypothalamic structures. The study demonstrated that visfatin gene and protein expression in MBH and POA depends on hormonal status related to the phase of the estrous cycle or early pregnancy. Blood plasma concentrations of visfatin during the estrous cycle were higher on days 2–3 in relation to other studied phases of the cycle, while during early pregnancy, the highest visfatin contents were observed on days 12–13. This study demonstrated visfatin expression in the porcine hypothalamus and its dependence on the hormonal milieu related to the estrous cycle and early pregnancy.